Dear life : stories - Munro, Alice, 1931- (New York : Vintage International, 2013)
This collection of stories illuminates moments that shape a life, from a dream or a sexual act to simple twists of fate that turn a person out of his or her accustomed path and into another way of being. Set in the countryside and towns of Lake Huron, these stories about departures and beginnings, accidents, dangers, and homecomings both virtual and real, paint a portrait of how strange, dangerous, and extraordinary the ordinary life can be.
To reach Japan -- Amundsen -- Leaving Maverley -- Gravel -- Haven -- Pride -- Corrie -- Train -- In sight of the lake -- Dolly -- The eye -- Night -- Voices -- Dear life.
Keywords: Short stories, Canadian; Huron, Lake (Mich. and Ont.) -- Fiction; Short stories